2018
DOI: 10.1002/aur.2015
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media, antibiotics, and risk of autism spectrum disorder

Abstract: Otitis media infections and antibiotic treatment have been linked to the risk of developing autism spectrum disorder. Broad‐spectrum antibiotics may alter the composition of the gut flora microbiota, which is hypothesized to be involved in the regulation of the immune system. This study examines the interplay among otitis media, antibiotics, and the subsequent risk of developing autism. Based on the entire Danish population, 780,547 children were followed from birth (January 1, 1997 to December 31, 2008) until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
0
33
1
1
Order By: Relevance
“…An earlier population‐based cohort study revealed that antibiotic use during pregnancy is associated with a 50%‐100% increase in ASD risk, while according to a recent large prospective cohort study, otitis media and the administration of broad‐spectrum antibiotics during early childhood increase ASD risk. However, in this latter investigation, there was no significant synergistic effect of otitis media and antibiotic use, suggesting that antibiotics did not modify the association between infection and ASD . Contrary to these findings, another large cohort study failed to reveal any significant association between antibiotic use during infancy and ASD risk .…”
Section: The Role Of Gut‐microbiota In Autism‐related Social Deficitscontrasting
confidence: 69%
“…An earlier population‐based cohort study revealed that antibiotic use during pregnancy is associated with a 50%‐100% increase in ASD risk, while according to a recent large prospective cohort study, otitis media and the administration of broad‐spectrum antibiotics during early childhood increase ASD risk. However, in this latter investigation, there was no significant synergistic effect of otitis media and antibiotic use, suggesting that antibiotics did not modify the association between infection and ASD . Contrary to these findings, another large cohort study failed to reveal any significant association between antibiotic use during infancy and ASD risk .…”
Section: The Role Of Gut‐microbiota In Autism‐related Social Deficitscontrasting
confidence: 69%
“…Four of those studies were cohort studies, and seven of them were case–control studies. Among the included cohort studies, three Danish studies (Atladottir et al 2012; Wimberley et al 2018; Axelsson et al 2019) were performed in overlapping populations. Five studies examined prenatal antibiotic exposure, five assessed early childhood antibiotic exposure and 1 study examined both types of exposure (Wimberley et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included cohort studies, three Danish studies (Atladottir et al 2012; Wimberley et al 2018; Axelsson et al 2019) were performed in overlapping populations. Five studies examined prenatal antibiotic exposure, five assessed early childhood antibiotic exposure and 1 study examined both types of exposure (Wimberley et al 2018). In the majority of included studies, use of any antibiotic, for any indication and duration and at any dose within the defined time period, was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the aetiology of the nutritional and GI problems of ASD remains unknown (McElhanon et al, 2014;Ferguson et al, 2016;Martínez-González and Andreo-Martínez, 2019) and everything seems to indicate that it is a combination of associated factors (Buie, 2015). Other authors suggest that abnormal GM in ASD may be caused by the overuse of antibiotics (Sandler et al, 2000;Krajmalnik-Brown et al, 2015;Wimberley et al, 2018) or a pathophysiological cascade of interactions between environmental factors and key genes. In addition, the neurological alterations associated with atypical growth of the head in children with ASD during the uterine period, which occurs more frequently in late gestations, can also be a possible trigger of ASD (Bonnet-Brilhault et al, 2018).…”
Section: Introductionmentioning
confidence: 99%